REPRESENTASI NILAI-NILAI ISLAM DALAM FILM TITIP SURAT UNTUK TUHAN : (ANALISIS SEMIOTIKA ROLAND BARTHES) - Windi Cahyani; Sunaryanto (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
This study aims to explore the representation of Islamic values in the film Titip Surat Untuk Tuhan. The focus of this research is to examine how the theme is implicitly conveyed through the film. The study employs a descriptive qualitative method using Roland Barthes' semiotic approach, which analyzes three levels of meaning: denotation, connotation, and myth. The analysis is conducted by identifying the representation of Islamic values within the film in order to reveal the underlying meanings embedded in its narrative. The film strongly represents Islamic values through Barthes’ three layers of meaning. At the denotative level, it portrays the daily lives of Muslims and their religious practices. At the connotative level, it conveys moral messages such as patience, sincerity, compassion, and gratitude. At the mythological level, the film constructs an ideal concept of Islamic life, where religion serves as a foundation for moral decision-making, social interaction, and views on life and death. Religious messages are delivered symbolically through scenes, characters’ emotional expressions, settings, and visual elements notably, the letter to God serves as a metaphor for human hope and prayer. Overall, the film functions not only as entertainment but also as an effective medium of Islamic preaching (dakwah), delivering spiritual messages in a humanistic and educational manner.